Directed solutions to address differences in access to liver transplantation. Issue 11 (24th May 2018) - Ye, Fei; Sheng, Quanhu; Feurer, Irene D.; Zhao, Zhiguo; Fan, Run; Teng, Jing; Ping, Jie; Rega, Scott A.; Hanto, Douglas W.; Shyr, Yu; Karp, Seth J.
Abstract : The United Network for Organ Sharing recently altered current liver allocation with the goal of decreasing Model for End‐Stage Liver Disease (MELD) variance at transplant. Concerns over these and further planned revisions to policy include predicted decrease in total transplants, increased flying and logistical complexity, adverse impact on areas with poor quality health care, and minimal effect on high MELD donor service areas. To address these issues, we describe general approaches to equalize critical transplant metrics among regions and determine how they alter MELD variance at transplant and organ supply to underserved communities. We show an allocation system that increases minimum MELD for local allocation or preferentially directs organs into areas of need decreases MELD variance. Both models have minimal adverse effects on flying and total transplants, and do not disproportionately disadvantage already underserved communities. When combined together, these approaches decrease MELD variance by 28%, more than the recently adopted proposal. These models can be adapted for any measure of variance, can be combined with other proposals, and can be configured to automatically adjust to changes in disease incidence as is occurring with hepatitis C and nonalcoholic fatty liver disease. Abstract : This article describes general approaches to equalize chosen transplant metrics across the country, minimize unwanted consequences, and preserve local allocation.